Achieving SDG 6 in Nepal: A Focus on Sanitation Access in Urban vs. Rural Makawanpur - Dhital, Krishna Prasad; Hans, V. Basil (NPRC Journal of Multidisciplinary Research, 2025)
Background & Objective: Access to adequate sanitation is a fundamental human right and essential for public health. This study investigates the disparities in sanitation access and quality between urban and rural areas in Makawanpur District, Nepal. Despite significant improvements, recent reports indicate a lack of comprehensive sanitation services, particularly in rural settings. The objective is to assess the types of sanitation facilities used, the quality of waste management services, and the satisfaction levels among households. Methodology: A descriptive research design was employed, utilizing a quantitative approach through structured questionnaires. A total of 200 respondents were randomly selected from both urban and rural households. Cross-tabulation analysis and Chi-square tests were conducted to determine statistical significance and compare sanitation indicators between the two settings. Results: Findings indicate that while 97.7% of urban households access piped water, only 91.7% of rural households do the same. Moreover, a concerning 53.8% of rural households lack access to solid waste collection services, contrasted with 9.1% of urban households. Furthermore, satisfaction levels regarding sanitation services were significantly higher in urban areas, with 9.1% rating sanitation as excellent compared to 3.2% in rural areas. Conclusion & Recommendation: There exist significant disparities in sanitation access and quality between urban and rural areas in Makawanpur District. The study recommends targeted interventions to enhance rural sanitation infrastructure, empower local governments, and implement community-based initiatives to promote responsible sanitation practices and improve overall public health.